APPLICATION OF DISCUSSION METHODS IN PAI LEARNING STATE ELEMENTARY SCHOOL 056642 KAMPUNG BARU - Nurlia, S.Pd (Journal of Educational Science Learning and Research, 2024)
There are many teaching methods applied by teachers in schools. One of them is the discussion method. This method emphasizes interaction between fellow students and also teachers in discussing or finding solutions to learning materials. If implemented properly, this discussion method can stimulate students to think or express their own opinions so that it will also train students to think critically and confidently. In Islamic religious education learning, the discussion method is not just an ordinary conversation or debate, but discussions arise because there are problems that require various answers or opinions. This is necessary for students in the future, not only because humans are always faced with various problems that cannot be solved alone, but also because through cooperation or deliberation a better solution may be obtained. The application of the discussion method carried out by students, especially with the guidance of teachers in Islamic religious education learning, is believed to be one of the right methods in channeling useful knowledge and deeper understanding